How Children Learn to Speak: A Psycholinguistic Analysis of Language Development in a Three-Year-Old (Universitas Pamulang, 2025)
This case study explores the early stages of language development in a three-year-old Indonesian-speaking child through the lens of psycholinguistics, focusing on phonological, morphological, and semantic domains. Drawing on the theoretical frameworks of Chomsky’s Universal Grammar, Halliday’s functional language theory, and Clark’s interactionist model, the research investigates how innate capacities and environmental input jointly shape language acquisition. Using naturalistic observation and audio-visual recordings, 25 spontaneous utterances were collected and analyzed qualitatively. Phonologically, the child demonstrated common developmental processes such as substitution and omission, showing partial mastery of the phonemic inventory. Morphological analysis revealed early morpheme use, overgeneralization, and bilingual word blending. Semantically, the child exhibited notable competence in categorization, antonym recognition, and pragmatic usage, often preceding phonological or morphological precision. The findings indicate that semantic understanding tends to develop earlier and more robustly than formal linguistic structures, underscoring the importance of a rich linguistic environment. This study highlights the intertwined roles of biological endowment and social interaction in early language learning and offers insight into the dynamic trajectory of linguistic development in early childhood.